Do Interactions Between Environmental Chemicals and the Human Microbiome Need to Be Considered in Risk Assessments?. Issue 11 (9th May 2019) - Rodricks, Joseph; Huang, Yvonne; Mantus, Ellen; Shubat, Pamela
Abstract: One of the most dynamic and fruitful areas of current health‐related research concerns the various roles of the human microbiome in disease. Evidence is accumulating that interactions between substances in the environment and the microbiome can affect risks of disease, in both beneficial and adverse ways. Although most of the research has concerned the roles of diet and certain pharmaceutical agents, there is increasing interest in the possible roles of environmental chemicals. Chemical risk assessment has, to date, not included consideration of the influence of the microbiome. We suggest that failure to consider the possible roles of the microbiome could lead to significant error in risk assessment results. Our purpose in this commentary is to summarize some of the evidence supporting our hypothesis and to urge the risk assessment community to begin considering and influencing how results from microbiome‐related research could be incorporated into chemical risk assessments. An additional emphasis in our commentary concerns the distinct possibility that research on chemical–microbiome interactions will also reduce some of the significant uncertainties that accompany current risk assessments. Of particular interest is evidence suggesting that the microbiome has an influence on variability in disease risk across populations and (of particular interest to chemical risk) in animal and human responses to chemical exposure. The possible explanatory power of the microbiome regarding sources of variability could reduce what might be the most significant source of uncertainty in chemical risk assessment.